Rencana Bisnis Penyedia Layanan Data Center Untuk Pelanggan Korporasi - , Doan Ramjani; , John Suprihanto, Dr., M.I.M. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Data for some companies is not considered important because the data is often considered only troublesome to acquire and manage them. But far above functions, the data is the absolute capital of a business success strategy. A company that has a complete data will easily beat the market and beat competitors. Companies should be aware that the data is very important for the continuity of their business thus should be considered to have a data center that can ensure data security company. Data Center is a facility that is used for placement of a set of servers or computer systems and data storage systems (storage) are conditioned by setting the power supply, air-conditioning, fire prevention, and usually also equipped with physical security systems (eg access control). Data Center must be equipped with adequate support device (PAC, UPS, Security System, Fire suppression) to ensure continuity of operations. This thesis is structured to answer the needs of the corporate segment will be a service provider's data center that could serve the security of corporate data business people from things that are not desirable, such as natural disasters, riots and hacking so that business can keep running and generating profits. Business Plan that is used in this thesis is the method of the business plan by Robert Hisrich, Michael P Peters, and Dean A Shepherd. This method will describe the risks in the face as well as contingency plans to address these risks. Data collection method used in this thesis are interviews with those who expert and gather supporting data for the formation of the company. Results from the provision of a Business Plan in this thesis is the Business Plan which can be a guideline or guide business development in 3 (three) to 5 (five) years into the future, the source of information on which the approval or whether investors or creditors to provide operating funds, as well as motivator to improve business performance on an ongoing basis which involves the entire company's organizational. This business plan can also be used as a benchmark in the evaluation by comparing the achievement of objectives in real terms and according to the Business Plan.